"This is our next problem": Cleaning up from the COVID-19 response. (1st May 2020) - Kalina, Marc; Tilley, Elizabeth
Highlights: The Covid-19 pandemic will produce an immense amount of waste to be managed. The waste impact of our socio-cultural responses to disasters is poorly understood. The waste impact of disasters, will increase due to climate change. We propose several research pathways on waste impacts of our response to COVID-19. Abstract: The purpose of this discussion is to highlight the essential role that solid waste management must play in a humanitarian response towards disasters, in particular the ongoing Covid-19 pandemic. We highlight a number of potential avenues for scholarly investigation into the waste impacts of our response to Covid-19, but in particular, briefly unpacks the relationship between disasters, consumption and disposability as one potential research topic. The discussion is intended to start a conversation that is, at the moment, critically relevant, and to contribute to a more inclusive, and less normatively Western waste management studies discourse.